현대 패션사진에서 보이는 디지털 변형의 표현유형과 미적 의미 - 강준호; Kang¸ Jun Ho; 권기영; Kwon¸ Gi Young (기초조형학연구, 2021)
본 연구의 목적은 디지털 기술을 통해 다채로운 변형 이미지를 활용하고 있는 현대 패션사진의 표현 유형을 분석하여 미적 의미를 도출하는데 있다. 연구 방법은 이론적 배경으로 변형과 관련된 문헌조사를 실시하였으며, 디지털 변형의 사례가 나타난 패션사진을 국내외 전문서적과 관련 저널, 외국서적, 인터넷 사이트 자료를 통해 수집하여 사례분석을 수행하였다. 현대 패션사진은 시각적 정보뿐만 아니라 이미지, 콘셉트, 메시지 등을 수용자에게 제공하는 전통적 커뮤니케이션의 방법으로, 디지털 기술을 통해 과거와 다른 변형된 모습의 가상 이미지로 표출된다. 이로 인해 현대 패션사진은 단순한 브랜드 홍보 수단을 넘어 예술적 측면에서도 가치를 인정받는 등 인식의 변화와 더불어 역할이 확장되고 있다. 현대 패션사진에서 보이는 디지털 변형의 표현 유형은 프레임의 구도를 파기하여 분해된 인체와 시공간의 이질적인 요소를 접목한 분해조립형과 실제 이미지를 생략한 후 주제를 간결한 이미지로 표현한 단순그래픽형으로 나타난다. 다음으로 이미지를 중첩, 확장한 과장형, 마지막으로 환경의 변형으로 부조리함을 연출한 상황왜곡형으로 범주화된다. 이를 통해 현대 패션사진에서 보이는 디지털 변형은 피상적 현상과 내재된 개념의 가상적 재현이라는 미적 의미를 가지고, 기술적 상상을 통해 독특한 조형미를 가지는 유희적 예술성을 발현한다. 그리고 패션사진의 대상을 디지털 이미지로 전환하여 분해, 강조, 왜곡 등의 변형으로 표현영역을 확장함으로써 탈경계적 조형미를 생성한다는데 의미가 있다. 이처럼 디지털 변형을 접목한 패션사진은 실재와 가상을 혼합하는 기술적 방식과 창작자의 자의식이 내포된 개념적 미학이 통합된 새로운 형식의 조형예술로서, 표현영역의 확장과 패션 이미지가 지닌 속성을 발현하는 창작의 도구로 활용될 것이라 기대한다. The purpose of this study is to analyze the expression type of modern fashion photography and derive aesthetic meaning with digital transformation. The research method was through investigating literature related to the transformation and analyzing the case by collecting fashion photographs showing cases of digital transformation with domestic and foreign professional literature, and internet sites. Modern fashion photography is a traditional method of communication that provides images, concepts, and messages to recipients as well as visual information, and is presented as a virtual image that is different from the past through digital technology. As a result, modern fashion photography is recognized for its artistic value and its role expands. The types of digital variations shown in modern fashion photographs appear as simple graphics types that visually omit the actual image and express the characteristics of the subject after destroying the frame's composition and incorporating disparate elements between the divided spaces. It is categorized as an exaggeration emphasized by the image components, and as a distortion type with irrational situations represented by distorted images through distortion of the body, clothing, and environment. The aesthetic meaning of digital transformation in modern fashion photographs has the meaning of virtual reproduction of phenomena and concepts, and expresses playful artistry through technical imagination. In addition, it is meaningful to expand the expression area and create transgressive formative beauty by transforming the object of fashion photography into a digital image. Fashion photography with digital transformation is a new way of formative art that integrates technological methods of mixing reality and virtual reality with conceptual aesthetics, and is expected to be used as a tool for creation to expand the expression area and express fashion properties.